If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + 12 = 5(5x + 4) Reorder the terms: 12 + 26x = 5(5x + 4) Reorder the terms: 12 + 26x = 5(4 + 5x) 12 + 26x = (4 * 5 + 5x * 5) 12 + 26x = (20 + 25x) Solving 12 + 26x = 20 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 12 + 26x + -25x = 20 + 25x + -25x Combine like terms: 26x + -25x = 1x 12 + 1x = 20 + 25x + -25x Combine like terms: 25x + -25x = 0 12 + 1x = 20 + 0 12 + 1x = 20 Add '-12' to each side of the equation. 12 + -12 + 1x = 20 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 20 + -12 1x = 20 + -12 Combine like terms: 20 + -12 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| 10-(2*-4)+3x=16 | | (5u+3)(5-u)=0 | | 3x+9-2x=14 | | 2x-6x+9=x-6+15 | | (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 | | 9x^2+169=0 | | 3x+9x-4=3(4x+9) | | -8=-(-6x-3) | | .5x-4=0 | | 2y+2(y-6)=8y-6(y-10) | | 9(x-1)=-126 | | 7/36*x=5 | | 4(x-2)=2x-2 | | 52=p-41 | | -(8x-4)-(3x-5)+10=-9(x-1)-(5x+8+3) | | 7x-2+5=10x+4 | | p+13=-10 | | 6x+9-5x=16 | | -2(3x-6)+5=-1 | | 8y=5y+9 | | Rx+Sy=Tfory | | (-5+7i)+(-8-9i)=0 | | (x)=3x+4 | | x-9/5-1=x-3/4 | | 5x-11=4x+6 | | 4w-6w=12 | | 9x-15=6x | | X-3/4(2x-12)=7x/2+5 | | 7x-12-4x=5x-7 | | f(x)=3x+36 | | 27/8(29/6k+1/4)=-4149/32 |